2021
DOI: 10.1038/s41467-021-26818-3
|View full text |Cite
|
Sign up to set email alerts
|

Full-color enhanced second harmonic generation using rainbow trapping in ultrathin hyperbolic metamaterials

Abstract: Metasurfaces have provided a promising approach to enhance the nonlinearity at subwavelength scale, but usually suffer from a narrow bandwidth as imposed by sharp resonant features. Here, we counterintuitively report a broadband, enhanced second-harmonic generation, in nanopatterned hyperbolic metamaterials. The nanopatterning allows the direct access of the mode with large momentum, rendering the rainbow light trapping, i.e. slow light in a broad frequency, and thus enhancing the local field intensity for boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…The absorption ( A ) of the samples is calculated according to A = 1 – T – R . An increase in the absorption suggests higher Ohmic losses and increased localized fields, which can potentially lead to a stronger nonlinear response as previous studies have reported. …”
Section: Resultsmentioning
confidence: 61%
“…The absorption ( A ) of the samples is calculated according to A = 1 – T – R . An increase in the absorption suggests higher Ohmic losses and increased localized fields, which can potentially lead to a stronger nonlinear response as previous studies have reported. …”
Section: Resultsmentioning
confidence: 61%
“…1. Recent years, HMMs have been demonstrated the ability in ultrabroadband and anisotropic absorption, 23,24 negative refraction, 25,26 enhancing second harmonic generation, 27 and many advanced applications. [28][29][30] NHMM exhibits anisotropic optical properties, which can be approximately described using the effective medium theory (EMT).…”
Section: Bpp In Nhmmsmentioning
confidence: 99%
“…In the past few decades, great efforts have been made to investigate GSP in different types of metallic structures, including flat metal films separated by a dielectric layer, [2][3][4] coupled metal nanoparticles, 5 metal nanoparticles on flat metal film structures (MNOF), [6][7][8] and their derivatives. 9,10 Various novel plasmonic phenomena, such as nonlocality, 11,12 huge electromagnetic enhancements, 13 ultra-strong coupling, 14,15 quantum tunneling, 16,17 and charge-transfer plasmons, 18 have been revealed, leading to a few interesting applications like surface-enhanced Raman scattering (SERS) with sensitivity down to the single-molecule level, 19,20 photothermal cancer therapy, [21][22][23] super-continuum generation, 24,25 and plasmon-enhanced electron emission. [26][27][28][29][30] In comparison with GSP modes from free-standing coupled metallic nanoparticles or MNOF, planar coupled nanostructures supported on a flat substrate are more favorable for device applications for the following reasons: (i) planar architectures can be facilely integrated with other functional components; (ii) the gap formed by planar structures is more easily accessed.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, great efforts have been made to investigate GSP in different types of metallic structures, including flat metal films separated by a dielectric layer, 2–4 coupled metal nanoparticles, 5 metal nanoparticles on flat metal film structures (MNOF), 6–8 and their derivatives. 9,10 Various novel plasmonic phenomena, such as non-locality, 11,12 huge electromagnetic enhancements, 13 ultra-strong coupling, 14,15 quantum tunneling, 16,17 and charge-transfer plasmons, 18 have been revealed, leading to a few interesting applications like surface-enhanced Raman scattering (SERS) with sensitivity down to the single-molecule level, 19,20 photothermal cancer therapy, 21–23 super-continuum generation, 24,25 and plasmon-enhanced electron emission. 26–30…”
Section: Introductionmentioning
confidence: 99%